The life of the ocean - Berrill, N. J. (Norman John), 1903- (New York : McGraw-Hill, 1966)
Text and color photographs introduce the wide variety of plants and animals of the oceans and their interrelationships.
"Published in cooperation with the World book encyclopedia."
Includes bibliographical references (page 227).
Donated By Akbar Ali Khan
Keywords: Marine biology; Science